Metabolic And Genetic Aspects of Diabetic Nephropathy (Texas Journal of Medical Science, 2024)
It is an undeniable fact that in DN caused by T2DM, a clearly defined "preclinical" (latent) stage of development is distinguished, where clinical symptoms are absent, and only functional and laboratory changes characterizing kidney function are detected. It is also undeniable that only early stages of DN can undergo reverse development. The article discusses the clinical and genetic aspects of diabetic nephropathy and their relationship at the early stages of the disease, as well as the combined influence of metabolic and genetic factors on the development of the disease. The results of our study suggest that the eNOS3 gene plays an important role in the development of DN in patients with type 2 diabetes in the studied Uzbek population